Perlindungan Hukum Korban Kejahatan Siber dalam Tindak Pidana Perjudian Online di Indonesia - Sahat Maruli Tua Situmeang; Wahyudi Wahyudi; Musa Darwin Pane (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
Online gambling in Indonesia has become a massive cybercrime, with financial turnover reaching IDR 976.8 trillion during 2017–2025. Behind these figures lie individual and family victims suffering material and immaterial losses, yet they are often positioned as offenders rather than protected parties. This study aims to analyze the legal framework for protecting online gambling victims, identify juridical and factual constraints in its implementation, and formulate an ideal protection model. The research employs a normative juridical method with statutory, case, and conceptual approaches. The findings indicate that Indonesian positive law does not recognize online gambling players as "victims" entitled to restitution and rehabilitation; instead, they face criminal threats under Article 303 bis of the Criminal Code and Article 27 of the ITE Law. Key constraints include the absence of an explicit definition, social stigma, weak recovery mechanisms, and minimal inter-agency coordination. This study recommends regulatory revision to distinguish between operators and victim-players, expansion of the victim definition under the Witness and Victim Protection Law (UU LPSK), and the establishment of integrated complaint and rehabilitation services under the coordination of the Ministry of Communication and Informatics (Kemenkominfo) and BSSN.